(untitled) (Marketing Journal, 2025)
This article describes the content of the concept of marketing logistics, the relevance of developing marketing logistics in wholesale trade, the main parameters of marketing logistics as a result of the symbiosis of marketing and logistics in wholesale trade, and the main tasks of marketing and logistics in wholesale trade.